Fracture damage and energy dissipation of granite based on continuous-discontinuous coupling - Run-Zhi Jia; Hong-Jie Duan; Meng-Zhen Su; Xiao-Zhi Liu; Yun-Juan Chen (PLoS ONE, 2025)
A three-dimensional continuous-discontinuous numerical model was established through FLAC3D-PFC3D simulation coupling to study the fracture damage and energy dissipation characteristics of granite under varying confining pressures, based on X-ray diffraction and laboratory mechanical tests. The results demonstrated strong agreement between the simulation outcomes of the coupling model and the laboratory experiments, particularly concerning mineral composition. At approximately 65% of the peak strength of granite, internal cracks emerged and propagated rapidly around particles with weaker strength, resulting in the formation of primary “X” type cracks that diagonally penetrated the rock sample, accompanied by secondary tensile cracks. As the confining pressure increased, the ratio of tensile cracks in rock sample failure decreased, while the ratio of shear cracks increased. This transition from brittle to plastic failure in granite was effectively inhibited by confining pressure, which altered the failure process. Interestingly, granite exhibited a consistent energy evolution pattern under varying confining pressures. Prior to reaching peak strength, energy accumulation predominated, shifting to dissipation and release after the peak was surpassed. Notably, the impact of confining pressure on fthe elastic deformation energy of the rock mass was more significant than on dissipative deformation energy.